Empowering Traditional Fisherwomen in Makassar's Outer Islands: Enhancing Knowledge and Skills for Sustainable Practices - Kamaruddin, Umar; Arda; Sumandiyar, Adi; Thamrin, Asbulla; Lagaligo S., Susanty I Mutia (CV. Literasi Indonesia, 2024)
This research aims to obtain in-depth information about the skills of traditional fisherwomen in processing marine products, and the knowledge of fisherwomen groups is very minimal as a reaction of humans to stimuli by the surrounding nature. The type of research is descriptive qualitative with data analysis carried out in four stages; data collection, data reduction, data presentation, and conclusion drawing. Additionally, data triangulation is used to strengthen the findings. The study reveals that to enhance the skills of fisherwomen on both islands in processing seafood, focused training sessions and group assistance are essential. These efforts aim to improve their capacity to utilize fish resources to create products such as shredded fish, fish nuggets, and fish balls, which can serve as a valuable source of supplementary income. Moreover, the limited knowledge of these fisherwomen indicates the need for further support, particularly in introducing techniques for effective product marketing. By facilitating both skill-building and marketing strategies, this research highlights the potential for empowering fisherwomen through initiatives that not only enhance their productivity but also contribute to the economic sustainability of their communities.